Evaluation of use of no-load windscreens in body of flow accelerator for wind power plants with vertical axis of rotation - A. A. Bubenchikov; Т. V. Bubenchikova (Омский научный вестник)
The article presents studies aimed at determining the design of a concentrator with the maximum airflow acceleration. In the course of the work, the tower-type installations with free blades in the body of the concentrator are investigated to determine the useful effect of their use. Analytical and experimental studies of the proposed structures and a version of their multi-tier design are carried out. Recommendations on the application of the proposed developments are given.